2021
DOI: 10.5144/0256-4947.2021.63
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Enterobacterales in thirteen tertiary care hospitals in Saudi Arabia

Abstract: BACKGROUND: Carbapenems are the antibiotics of last-resort for the treatment of bacterial infections caused by multidrug-resistant organisms. The emergence of resistance is a critical and worrisome problem for clinicians and patients. Carbapenem-resistant Enterobacterales (CRE) are spreading globally, are associated with an increased frequency of reported outbreaks in many regions, and are becoming endemic in many others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The majority of CRE is Klebsiella pneumoniae, which are carbapenem resistant due to the production of carbapenemases (CRKP) [2]. This worldwide trend is also observed in countries of the Arabian Peninsula [3][4][5]. Spread of CRKP is mainly driven by clonal dissemination of so called high-risk multi-drug resistant (HiR MDR) clones [2].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of CRE is Klebsiella pneumoniae, which are carbapenem resistant due to the production of carbapenemases (CRKP) [2]. This worldwide trend is also observed in countries of the Arabian Peninsula [3][4][5]. Spread of CRKP is mainly driven by clonal dissemination of so called high-risk multi-drug resistant (HiR MDR) clones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our study, previous studies showed that OXA-48 was the most common gene encoding for carbapenemase- producing K pneumoniae in the Kingdom of Saudi Arabia ranging between 68% and 78% of all carbapenemase genes. 16 , 34 , 35 Moreover, in one study, all OXA-48 carbapenemase-producing Enterobacterales were susceptible to CAZ-AVI with good profile for safety and effectiveness. 36 This emphasizes the importance of having CAZ-AVI formulary available in all hospitals in the Kingdom and to be used over colistin-based regimen for the treatment of infections caused by CRE.…”
Section: Discussionmentioning
confidence: 99%
“…carbapenemase genes. 16,34,35 Moreover, in one study, all OXA-48 carbapenemase-producing Enterobacterales were susceptible to CAZ-AVI with good profile for safety and effectiveness. 36 This emphasizes the importance of having CAZ-AVI formulary available in all hospitals in the Kingdom and to be used over colistin-based regimen for the treatment of infections caused by CRE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of reporting is probably the reason. Klebsiella pneumoniae is the most reported CRE species in Saudi Arabia with a prevalence of 88% followed by E. coli at 11% [5,19,20]. NDM and OXA-48 enzymes are the major carbapenemases causing resistance in Enterobacteriaceae reported from the Gulf region and Saudi Arabia [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%